Histopathological Changes Caused by Inflammation and Oxidative Stress in Diet-Induced-Obese Mouse following Experimental Lung Injury - Wang, Fengyuan (Sci Rep, 2018)
Obesity has been identified as a risk factor for adverse outcomes of various diseases. However, information regarding the difference between the response of obese and normal subjects to pulmonary inflammation is limited. Mice were fed with the control or high-fat diet to establish the lean and diet-induced obese (DIO) mice. Escherichia coli was intranasally instilled to reproduce non-fatal acute pneumonia model. After infection, serum samples and lung tissues were obtained at 0, 12, 24, and 72 h. DIO mice exhibited increased serum triglyceride (TG) and total cholesterol (TC) contents as well as pulmonary resistin, IL-6, and leptin levels compared with lean mice. E. coli infection caused an acute suppurative inflammation in the lung with increased lung index and serum TG and TC contents; elevated pulmonary tumor necrosis factor-α, interleukin (IL)-1β, IL-6, IL-8, and leptin levels; and oxidative stress in mice. Interestingly, almost all the above-mentioned parameters peaked at 12 h after infection in the lean-E. coli group but after 12 h in the DIO-E. coli group. These results indicated that the DIO mice presented a delayed inflammatory response and oxidative stress in non-fatal acute pneumonia induced by E. coli infection.